Acreage Response to Prices of Major Crops in Ganganagar District of Rajasthan -An Econometric Analysis - Gajja, B L; Kalla, Jagdeesh C; Vyas, D L (Annals of Arid Zone, 2016)
An attempt has been made in this study to obtain the best estimates of the district acreage response to prices in major crops, viz., wheat, barley, rape and mustard; cotton and sugarcane in Ganganagar district of Rajasthan State. The Nerlovian lagged model with some modifications was employed in present context. Risk variable was included in the model alternatively in the forms of standard deviation and coefficient of variation of the relative profitability based on preceding three years. The results revealed that area allocation of major crops have been principalIy guided by relative profitability (PtÂ·1). The coefficient of variation proved to be a better proxy of risk than standard deviation. On the basis of this study it can be inferred that cotton, rape and mustard; and sugarcane are relatively high risk crops as compared to wheat and barley. Policy of rationalised output price-structure is thus prerequisite for stabilised productivity performance of major crops in arid areas endowed with assured irrigation.